Regulasi Tindak Pidana Ekonomi Dalam Kasus Perbankan Penyalahgunaan Wewenang - Pesman Laia; Hudi Yusuf (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
In the modern era marked by rapid digital innovation, the banking sector is undergoing a significant transformation through the application of digital technology that enhances accessibility, efficiency, and the reach of financial services. However, these advancements also bring new threats, including the abuse of authority within banking institutions. Such abuse can lead to substantial losses for customers, disrupt economic stability, and undermine public trust in the financial system. In this context, this research aims to conduct an in-depth analysis of the forms, scope, and impacts of authority abuse in the banking sector, as well as the effectiveness of existing regulations in preventing and addressing these cases. The study employs a case study methodology by collecting data from regulatory documents, government reports, and credible publications to explore various examples of authority abuse in Indonesia and internationally. Through this analysis, the research also identifies weaknesses in the existing legal framework and challenges in the synergy between supervisory authorities and financial institutions in creating a secure and integral banking ecosystem. The findings indicate that although there are several regulations established to prevent authority abuse, there are still legal gaps and enforcement challenges that criminals can exploit. These weaknesses are exacerbated by a lack of rules responsive to the developments in digital technology and weak oversight within banking institutions. Therefore, this research recommends the need for more adaptive regulatory updates, strengthening the oversight framework, and enhancing coordination among relevant authorities to build a banking system that is not only innovative but also secure for customers and stable for the economy.